Synthesis, biological evaluation and computational studies of pyrazole derivatives as Mycobacterium tuberculosis CYP121A1 inhibitors. Issue 11 (26th August 2022) - Alshabani, Lama A.; Kumar, Amit; Willcocks, Sam J.; Srithiran, Gayathri; Bhakta, Sanjib; Estrada, D. Fernando; Simons, Claire
Abstract : Pyrazole derivatives were evaluated using UV-vis and protein-detected 1D 19 F-NMR (Mtb CYP121A1 binding affinity), antimycobacterial determination (MIC) and computational studies illustrating the potential anti-TB properties of the compounds. Abstract : A series of imidazole and triazole diarylpyrazole derivatives were prepared using an efficient 5-step synthetic scheme and evaluated for binding affinity with Mycobacterium tuberculosis (Mtb) CYP121A1 and antimycobacterial activity against Mtb H37Rv. Antimycobacterial susceptibility was measured using the spot-culture growth inhibition assay (SPOTi): the imidazoles displayed minimum inhibitory concentration (MIC90 ) in the range of 3.95–12.03 μg mL −1 (10.07–33.19 μM) with 11f the most active, while the triazoles displayed MIC90 in the range of 4.35–25.63 μg mL −1 (11.88–70.53 μM) with 12b the most active. Assessment of binding affinity using UV-vis spectroscopy showed that for the imidazole series, the propyloxy (11f ) and isopropyloxy (11h ) derivatives of the 4-chloroaryl pyrazoles displayed Mtb CYP121A1 type II binding affinity with K d 11.73 and 17.72 μM respectively compared with the natural substrate cYY ( K d 12.28 μM), while in the triazole series, only the methoxy substitution with the 4-chloroaryl pyrazole (12b ) showed good type II Mtb CYP121A1 binding affinity ( K d 5.13 μM). Protein-detected 1D 19 F-NMR spectroscopy as an orthogonal strategy was used to evaluate ligand binding independent of perturbations at the haem. For imidazole and triazole compounds, perturbations were more intense than cYY indicating tighter binding and confirming that ligand coordination occurs in the substrate-binding pocket despite very modest changes in UV-vis absorbance, consistent with computational studies and the demonstrated potential anti-tuberculosis properties of these compounds.